Macroeconomic Determinants: The Mediating Effect of Net Income on Share Price - Ridhwan, Nugroho; Young, Felina C. (IJOSMAS, 2026)
This research focuses on analyzing the impact of exchange rate, interest rate, and inflation on share prices within Indonesia's industrial sector companies listed on the Indonesia Stock Exchange from 2012 to 2024, while excluding the COVID-19 pandemic era (2020-2022). Employing Structural Equation Modeling (SEM) and the Partial Least Squares (PLS) method through SmartPLS 4.0, the study examines five key variables, including net income as a mediating factor between the independent variables (exchange rate, interest rate, inflation) and the dependent variable (share price). The findings reveal that exchange rate volatility has a significant positive influence on net incomes reported by industrial firms. Conversely, interest rates negatively affect net income, suggesting that higher interest charges may hinder financial performance by increasing costs of borrowing. Interestingly, inflation does not significantly impact net income across the surveyed companies, indicating that other factors may mitigate inflation's effects within this context. Furthermore, the study shows that fluctuations in the exchange rate do not directly influence share prices, raising questions about the sensitivity of stock prices to macroeconomic variables in this industrial sector. Nevertheless, net income emerges as a critical determinant positively influencing share prices among the companies analyzed, corroborating the notion that financial performance is closely linked to market valuation. Additionally, the study demonstrates that while net income mediates the relationship between both exchange rate and interest rate with share prices, it does not serve as a mediator in the relationship between inflation and share prices. These results highlight the complexity of financial dynamics within Indonesia's industrial sector and underscore the importance of robust financial performance indicators in shaping market valuations. This research contributes to the broader understanding of investment dynamics in emerging markets, particularly by illuminating the unique interactions between macroeconomic factors and corporate financial health in Indonesia’s industrial sector.